Pengaruh Bauran Pemasaran Ritel Terhadap Keputusan Pembelian: Studi Kasus Pada Pelanggan Super Indo di Kota Bogor - Lina, Ade; Nurendah, Yulia (Jurnal Ilmiah Manajemen Kesatuan, 2022)
The purpose of this study was to analyze the influence of products, prices, distribution (physical facilities), promotions and purchasing decisions at Super Indo. The population in this study are all consumers who have made purchases at Super Indo. The sampling technique used was purposive sampling, with 100 respondents. Data were collected using a questionnaire as the main instrument, and the questionnaire used a Likert scale to measure respondents' answers. Data testing was performed using SPSS 22 software. The results of this study are as follows: (1) Product (X1) can be concluded that it has a positive effect (2,041> 1.98) on Purchasing Decisions (Y) and is significant. (2) Price (X2) can be concluded to have a positive effect (2,386> 1.98) on Purchasing Decisions (Y) and is significant. (3) Distribution (Physical Facilities) (X3) can be concluded as having a positive effect (2,386> 1.98) on Purchasing Decisions (Y) and significant. (4) Promotion (X4) can be concluded positive (0.457 <1.98) of the Purchase Decision (Y) and not significant. (5) Product (X1), Price (X2), Distribution (Physical Facilities) (X3), Promotion (X4) can simultaneously be concluded to have a positive effect (9,758> 2.47) on the Purchasing Decision (Y) and significant. Keywords: Product, Price, Distribution (Physical Facilities), Promotion, Purchase Decision